PEP Scan - A Tool for Assisting in the Identification of Potential Improper Benefits Receipt by PEPs in Brazil - Guijarro, Michel de O.; Toledo, Claudio F. M.; Camargo, Valter V. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: PEP Scan focuses on the use of technology to combat corruption in Brazil. Its primary objective is the monitoring of Politically Exposed Persons (PEP), aiming to prevent the misuse of public funds and strengthen transparency. Scientific and/or Practical Problem: There is a critical gap in public tools for integrating and analyzing heterogeneous government data. The core challenge lies in adapting data mining techniques to identify fraud, with a specific focus on uncovering complex connections. Proposed Solution and/or Analysis: The proposed solution is PEP Scan, a web-based tool that integrates public data. It employs a Breadth-First Search (BFS) algorithm and Visual Data Mining (VDM) techniques to map suspicious connections, enabling the exploration of patterns through an interactive graph interface. Related IS Theory: Pep Scan aligns with socio-technical IS theory by integrating technical innovations and user-centric needs. Research Method: The methodology involved the development of a prototype that integrated and processed public databases. The research core was the adaptation of the BFS algorithm to map connections. Two kinds of evaluation were performed: an analysis of the architectural quality and another related to usability, employing the heuristics proposed by Jakob Nielsen. Summary of Results: PEP Scan demonstrated its effectiveness by identifying PEPs who received benefits unduly, including over 400 city councilors. The tool also revealed indirect and complex connections, validating its capability to uncover non-trivial patterns. Contributions and Impact to IS area: This research provides a replicable model and a practical tool for combating corruption. The work contributes to the Information Systems field by demonstrating how technical rigor and a focus on usability can promote citizen science and strengthen public transparency.